(untitled) (Research, Society and Development, 2020)
The aim of this paper is to review and synthesize research focused on child sponsorship (CS) and, in doing so, to present a critique grounded in conceptualizations of justice, solidarity, ethical relationships, and international development education. As discussed in this paper, a review of the literature yields eight motivations for becoming involved in child sponsorship: Personal connection; altruism; guilt; small win; part of something bigger; distrust of government; not faceless; advancing development. Following the research synthesis and discussion of these motivations, a critique is constructed by viewing these motivations through three theoretical lenses: conceptualizations of the good citizen, the complex audience member and, finally, a pedagogical tool and framework referred to as HEADS UP. The paper concludes with questions centring on power, poverty, responsibility, complicity, justice and peace, and, ultimately, provides a response to the question of “is it better than nothing?” The argument put forth in this paper is that, in its noted absence of a more critical examination of the root causes of poverty and global injustices, child sponsorship is, in fact, not better than nothing.